In vitro anti-venom potential of various solvent based leaf extracts of Andrographis serpyllifolia (Rottler ex Vahl) Wight against Naja naja and Daboia russelli. (6th April 2021) - Hansiya, V.S.; Geetha, N.
Abstract: Ethnopharmacological relevance: Snake bite is a major occupational hazard in tropical and subtropical countries including India as per the World Health Organization. Naja naja (Indian cobra) and Daboia russelli (Russell's viper) are the two poisonous snakes commonly associated with human mortality in India. Andrographis serpyllifolia (Rottler ex Vahl) Wight has been documented in ethnobotanical records as a plant possessing potent anti-snake venom activity. Aim of the study: The present study is aimed for systematic evaluation of in vitro anti-venom potential of various solvent based leaf extracts of A. serpyllifolia against toxic venom enzymes of Naja naja and Daboia russelli . Materials and methods: Different solvent based leaf extracts of A . serpyllifolia were tested against the snake venoms of Naja naja and Daboia russelli obtained from Irula Snake Catchers Industrial Co-operative Society Limited, Kancheepuram, Tamil nadu, India. Three different in vitro neutralization assays such as indirect hemolysis, procoagulent and lytic activities and seven in vitro enzyme inhibition assays such as protease, acetylcholinesterase, phosphomonoesterase, phosphodiesterase, 5′nucleotidase, phospholipase A2, hyaluronidase and post synaptic acetylcholine receptor binding activity were carried out according to standard protocols. The results were analyzed using the standard ANOVA procedures. Results: Among various solvent based leaf extracts of A . serpyllifolia tested, aqueous extract showed maximum neutralizing and inhibitory activities against Naja naja and Daboia russelli venoms. Conclusions: The various in vitro enzymatic studies reveal that the aqueous leaf extract of A . serpyllifolia plant could inhibit most of the toxic enzymes of the Naja naja and Daboia russelli venoms which could be further confirmed by in vivo studies. Graphical abstract: Image 1